Aortic valve replacement with a new sutureless aortic valve Perceval S prosthesis: 12 months of Polish experience - Niklewski, Tomasz; Filipiak, Krzysztof; Przybylski, Roman; Zembala, Michał; Kukulski, Tomasz; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction : The increasing number of high-risk patients with narrow aortic root undergoing major cardiac surgery has led to the need for alternative treatment options and the development of new techniques for valve replacement. These patients have frequently multiple comorbidities that impose an increased risk of perioperative complications. Recent data from a multicenter registry have demonstrated a big success rate of transcatheter aortic valve implantation (TAVI) procedures. However, because of many adverse events it is necessary to introduce another device assigned for this group of patients. Implantation of a sutureless valve seems to be the right choice, especially those implanted from a miniinvasive approach. Aim of the study: The aim of the study was to analyze the implantation procedure, hemodynamic and clinical parameters of the new sutureless Perceval S valves and compare them to other prostheses implanted in a narrow aortic root. Material and methods : 14 Perceval S sutureless bioprosthetic valves were successfully implanted: eight valves size 23, four size 25, and two size 21. There were 3 early explantations by the surgeon’s decision because of valve malposition and unacceptable perivalvular leak. In those patients other bioprostheses were implanted. Eight implantations were made by minithoracotomy. All patients are alive. In the postoperative period most of the patients changed their NYHA class from III or II to I (72%) or II, with evident improvement of exercise capacity. The mean diameter of the native aortic annulus measured in TEE before the operation was 21.9 mm and the mean size of the implanted Perceval S valves was 23.9. Results : The mean transvalvular gradient changed significantly from 54.5 mmHg before the operation to 13 mm Hg in follow-up. The ejection fraction (EF) was the same before and in follow-up echo: 54.4 and 55%. The value of follow-up mean effective orifice area (EOA) calculated in follow-up transthoracic echo was 1.71 cm2, which is a very good value for biological aortic prostheses. The mean total extracorporeal circulation time was 39.2 and implantation time 8.9 minutes. We compared Perceval S sutureless prostheses with other stentless and mechanical valves in patients from our clinical material after aortic valve replacement (AVR) of isolated severe aortic stenosis and narrow aortic annulus, with good EF and without significant concomitant diseases in 12 months observation. Perceval S valves as well as SOLO stentless bioprostheses revealed the best performance in aortic position with significant improvement of NYHA class and good EOA in 12 months’ observation. In patients with AS and good LV function implantation of mechanical small prostheses intended for implantation in narrow roots (OnX©) gave in our observation borderline mismatch of these valves. Conclusion : Sutureless self-expandable Perceval S valves seems to be a promising future option for older patients with a lower logistic score (than for TAVI procedures) and small aortic annulus because of the possibility of implantation of a larger valve than the measured annulus with significant shortening of implantation time.